Mathematic simulation of transient process in a. c – system “electric – traction – network – locomotive” 2. Switch on the main locomotive’s power converter in “free pay” mode; definition and analysis current surge of magnetization - Mischenko, T. M. (Science and Transport Progress, 2011)
The article is a continuation of analysis of mathematical models for AC systems, in which the elements of electric-traction network and switch-on of power transformer in an idling mode are gradually connected. The numerical calculations and analysis of current of transformer magnetization are executed.